Design, fabrication, and validation of patient-specific electron tissue compensators for postmastectomy radiation therapy. (October 2018) - Craft, Daniel F.; Balter, Peter; Woodward, Wendy; Kry, Stephen F.; Salehpour, Mohammad; Ger, Rachel; Peters, Mary; Baltz, Garrett; Traneus, Erik; Howell, Rebecca M.
Abstract: Background and purpose: Postmastectomy radiotherapy (PMRT) is complex to plan and deliver, but could be improved with 3D-printed, patient-specific electron tissue compensators. The purposes of this study were to develop an algorithm to design patient-specific compensators that achieve clinical goals, to 3D-print the planned compensators, and validate calculated dose distributions with film and thermoluminescent dosimeter (TLD) measurements in 3D-printed phantoms of PMRT patients. Materials and methods: An iterative algorithm was developed to design compensators corresponding to single-field, single-energy electron plans for PMRT patients. The 3D-printable compensators were designed to fit into the electron aperture, with cerrobend poured around it. For a sample of eight patients, calculated dose distributions for compensator plans were compared with patients' (multi-field, multi-energy) clinical treatment plans. For all patients, dosimetric parameters were compared including clinical target volume (CTV), lung, and heart metrics. For validation, compensators were fabricated and irradiated for a set of six 3D-printed patient-specific phantoms. Dose distributions in the phantoms were measured with TLD and film. These measurements were compared with the treatment planning system calculated dose distributions. Results: The compensator treatment plans achieved superior CTV coverage (97% vs 89% of the CTV receiving the prescription dose, p < 0.0025), and similar heart and lung doses (p > 0.35) to the conventional treatment plans. Average differences between calculated and measured TLD values were 2%, and average film profile differences were <2 mm. Conclusions: We developed a new compensator based treatment methodology for PMRT and demonstrated its validity and superiority to conventional multi-field plans through end-to-end testing.